Physalis peruviana-Derived 4β-Hydroxywithanolide E, a Novel Antagonist of Wnt Signaling, Inhibits Colorectal Cancer In Vitro and In Vivo - Zhen-Nan Ye; Feng Yuan; Jie-Qing Liu; Xing-Rong Peng; Tao An; Xue Li; Ling-Mei Kong; Ming-Hua Qiu; Yan Li (Molecules, 2019)
Deregulation of the Wnt signaling pathway leads to colorectal cancer progression. Natural dietary compounds serve as promising candidates for development as chemopreventive agents by suppressing the Wnt/β-catenin signaling pathway. Physalis peruviana-derived 4βHWE showed a significant inhibitory activity with a calculated IC50 of 0.09 μΜ in a screening of novel inhibitors of Wnt signaling with the dual-luciferase reporter assay. This study investigated the anti-tumor effect of 4βHWE and the potential Wnt signaling inhibitory mechanism. Both the western blot analysis and immunofluorescence assay showed that 4βHWE promoted the phosphorylation and degradation of β-catenin and the subsequent inhibition of its nuclear translocation to attenuate the endogenous Wnt target gene expression in colorectal cancer (CRC) cells. The cell viability assay indicated that 4βHWE preferentially inhibited the proliferation of CRC compared with CCD-841-CoN, a normal human colonic epithelial cell line. 4βHWE-mediated G0/G1 cell cycle arrest and apoptosis induction contributed to the suppression of the proliferation of CRC in the cell cycle and Annexin V-FITC/Propidium Iodide apoptosis analysis. Moreover, in vivo, 4βHWE dramatically inhibited tumor growth in HCT116 xenografts by attenuating the Wnt/β-catenin signaling pathway. In conclusion, our study suggested that 4βHWE could be of potential use in anti-tumor agent development as a novel Wnt signaling inhibitor.